Vatican I : the council and the making of the ultramontane church - O'Malley, John W. (S.I.) (1927-2022) autor (The Belknap Press of Harvard University Press, 2018)
In the nineteenth century, the foundations upon which the Catholic Church had rested for centuries were shaken were shaken by liberalism. At the Vatican Council of 1869-1870, the church made a dramatic effort to set things right by defining the doctrine of papal infallibility. As a result, the church became more pope-centered than ever before